Crop improvements for future‐proofing European food systems: A focus‐group‐driven analysis of agricultural production stakeholder priorities and viewpoints. Issue 1 (12th December 2022) - Stetkiewicz, Stacia; Menary, Jonathan; Nair, Abhishek; Rufino, Mariana C.; Fischer, Arnout R.H.; Cornelissen, Marc; Duchesne, Remi; Guichaoua, Adrien; Jorasch, Petra; Lemarié, Stephane; Nanda, Amrit K.; Wilhelm, Ralf; et al.
Abstract: Crop breeding is one of the main tools which can assist in future‐proofing food systems for more sustainable outcomes. In order to ensure priorities are aligned with the needs and wants of food system actors, it is essential to engage with key stakeholders to understand preferences on plant breeding solutions. This study presents results from a series of online focus groups conducted with agricultural production related stakeholders (i.e. farmers and farmer representatives, policymakers and NGOs) regarding the potential for crop improvement to future‐proof European food systems. Stakeholders shared concern around climate change and environmental impacts (particularly drought and heat stress), and general agreement about the need to develop resilient crops which combine multiple positive attributes, while reducing trade‐offs and negative externalities. Stakeholders also prioritized plant breeding solutions for areas where they felt they had little agency, and existing alternative solutions, such as improving input use efficiency, or altering diets to be considered where these are available. This highlights the need for the crop breeding community to focus its attentions on the 'most hard to fix' issues, where in‐field measures are currently not offering viable solutions, to maximize acceptance and adoption by agricultural production stakeholders. It also highlights that consideration of trade‐offs, within plant and within a broader agri‐food context, must be integrated into crop breeding research and development, with trade‐off analysis an explicit component of breeding research. Understanding broader agri‐food system knock‐on effects of plant innovation is a non‐trivial challenge requiring interdisciplinary research and close partnerships with food system stakeholders. Abstract : Crop improvement priorities for future‐proofing the European food system were explored with farmers, farmer representatives, NGOs and policy stakeholders through a series of online focus groups. Several shared important issues were identified, including: climate change and environment, resilient crops to cope with multiple challenges, reducing trade‐offs and negative externalities in breeding and focusing plant breeding on areas where pre‐existing alternatives (e.g. improved farm management practice) do not already exist. The results of this study emphasize the need for integrated solutions to the complex challenges facing sustainable agricultural systems.